Reflexes of the pandemic on the economy of small cities: a look from the transport scenarios (Research, Society and Development, 2022)
The transports provide mobility and accessibility to people, being responsible for economic activities. Thus, this article aimed to characterize the transport scenarios of how people used them to move before the Covid-19 pandemic, how they're using them during the pandemic and how they intend to use them after this period is over. From the transport scenarios obtained, the impact of the pandemic on the economy of small cities was analyzed. For this, data were collected from a sample of the population through a questionnaire, using the Google Forms tool. After tabulating and analyzing the data obtained, it was observed that, before the pandemic, individuals used the means of transportation frequently. The main reasons for moving were to study, have leisure time and visit friends or family. However, during the pandemic, this scenario changed with the exacerbated decrease in the use of transport, causing economic activities, predominant in the central areas of small cities, to suffer a high reduction. People started to move only out of necessity due to the fear of being contaminated by Covid-19, prioritizing, thus, the activities of shopping, health and working. After this period is over, people intend to use the means of transportation more and more often than during the pandemic, causing, therefore, an increase in the circulation of individuals.